2022
DOI: 10.1371/journal.pone.0277129
|View full text |Cite
|
Sign up to set email alerts
|

Risky sexual behaviours among Ugandan university students: A pilot study exploring the role of adverse childhood experiences, substance use history, and family environment

Abstract: Background University students are known to have risky sexual behaviours (RSBs). The severity of the RSB is influenced by many factors, including the family environment, exposure to adverse childhood events (ACEs), and the use of addictive substances. However, there is limited information about the influence of ACEs and the family environment of these students in low-and medium-income countries (LMICs). Therefore, a pilot study was conducted among university students from a LMIC, Uganda. Methods The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
(99 reference statements)
2
12
0
Order By: Relevance
“…11, 20 Globally, studies have reported higher proportion of RSB among males as compared to females. 17, 18, 25 It has been noted that males tend to report higher sexual exposure than females, 15 similar observation was also made in this study. These difference of risky sexual behavior across gender could be attributed to many factors such as social desirability biases and sexual double standards such as women are expected to be virgin till marriage, and male’s masculinity is associated with sex.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…11, 20 Globally, studies have reported higher proportion of RSB among males as compared to females. 17, 18, 25 It has been noted that males tend to report higher sexual exposure than females, 15 similar observation was also made in this study. These difference of risky sexual behavior across gender could be attributed to many factors such as social desirability biases and sexual double standards such as women are expected to be virgin till marriage, and male’s masculinity is associated with sex.…”
Section: Discussionsupporting
confidence: 89%
“…11,20 Globally, studies have reported higher proportion of RSB among males as compared to females. 17,18,25 It has been noted that males tend to report higher sexual exposure than females, 15 similar observation was also made in this study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, respondents who consume substances such as smoking cigarette or chewing chat or consume hashish were approximately 3.5 times more likely to practice risky sexual behaviors than their counterparts. This was again supported by studies conducted among students at Madawalabu University ( 37 ), Bahir-Dar University ( 36 ), Debre Markos University ( 34 ), Uganda ( 49 ), Debre-Tabor University ( 31 ), and studies in nine Asian Countries ( 50 ). Usually, substance use and risky sexual behavior go hand in hand ( 51 ).…”
Section: Discussionmentioning
confidence: 71%